Aerogel catalyst with core-shell structure and preparation method and application thereof
The preparation of iron-nickel-based aerogel catalyst with a core-shell structure by wet chemical reduction method solves the problems of cumbersome preparation process and poor catalytic effect in the prior art, and achieves efficient and simple catalyst preparation and excellent catalytic performance.
Patent Information
- Application Number
- CN202411917174.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The preparation process of existing aerogel catalysts is cumbersome and costly, and has poor catalytic effects, making it difficult to promote in industrial large-scale production.
Through wet chemical reduction method, the reaction conditions were controlled using the mild reducing properties of dimethylammonium borane to prepare an iron-nickel-based aerogel catalyst with a core-shell structure, and combined with trace amounts of metal ruthenium as a reaction inducer, the in situ growth of FeNi3 alloy was achieved.
It realizes the rapid and simple preparation of high-purity iron-nickel metal salt catalysts, forming a tight interface structure, improving the catalytic performance and stability of the catalyst, and is suitable for OER catalysis of hydrogen production by electrolyzing water.
Smart Images

Figure CN119346119B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogel catalysts, and in particular relates to an aerogel catalyst with a core-shell structure and a preparation method and application thereof. Background Art
[0002] At the end of the 19th century, the global climate warmed, and with the advent of the industrial age, the greenhouse effect became more serious, including the burning of fossil fuels and the cutting of trees, which triggered a series of problems that threaten human survival. The non-renewable nature of fossil fuels further illustrates their great limitations, but the current global energy consumption is still dominated by fossil fuels. By 2019, non-renewable energy accounts for 84% of the total energy structure. Greenhouse gases produced by fossil fuels account for more than 75% of global greenhouse gas emissions and nearly 90% of all carbon dioxide emissions.
[0003] In this context, it has become an urgent desire to find green, renewable and sustainable energy to replace traditional fossil fuels. Hydrogen, as one of the most promising energy carriers in the future, has attracted widespread attention. Using renewable energy such as solar energy for water electrolysis is considered to be the most promising method for hydrogen production. However, the anodic oxygen evolution reaction (OER) has slow kinetic characteristics caused by 4-electron transfer, which greatly limits the efficiency of water electrolysis. Traditionally, Ir and Ru oxides are believed to be the most effective active catalysts for OER. FeNi bimetallic catalysts are hailed as one of the catalysts with broad prospects due to the Fe-Ni bimetallic synergy. They can not only break through the high price limit of precious metals, but also have excellent OER catalytic performance. Many scholars have carried out a series of studies on FeNi bimetallic catalysts.
[0004] Amorphous structure is an important part of promoting the rapid progress of OER reaction. High defect density can produce a large number of active sites, but due to the disordered lattice arrangement, amorphous structure has low conductivity. In addition, studies have shown that catalysts with both amorphous structure and long-range ordered crystal structure are highly competitive in the field of water electrolysis. Aerogels stand out in the field of catalysis with their unique nanoscale three-dimensional skeleton structure and high porosity. This is because the advantages of aerogel structure can provide more active sites and fast electron transfer pathways, as well as higher stability.
[0005] In the field of aerogel catalyst preparation, the main technologies currently used are hydrothermal method and sol-gel method. After the hydrogel is prepared first, aerogel is obtained through a series of drying methods such as environmental drying, freeze drying or supercritical drying. The preparation process of aerogels prepared by the hydrothermal method is cumbersome and often requires the synthesis of precursors. After obtaining the gel, metal crystals need to be grown on the aerogel by heat treatment or hydrothermal methods. The preparation of aerogels by the sol-gel method often requires precise control of multiple parameters during the preparation process. Finally, due to the addition of multiple reagents, it takes a long time to wash multiple times during the cleaning process. The above two methods of preparing aerogels have more process control links and higher costs, which are not conducive to industrial-scale production. In addition, the growth environment of the sol-gel method is relatively harsh and it is difficult to promote it in actual production.
[0006] At present, the two-phase synthesis method and the sacrificial template method are often used to prepare catalysts with shell-core structures. The two-phase synthesis method mainly prepares a crystalline core first, then combines the amorphous structure with the crystalline core, and finally forms a two-phase structure with an amorphous shell and a crystalline core. It is difficult to synthesize metal nanoparticles with a tight core-shell structure when preparing core-shell structure nanomaterials using a two-phase synthesis method, which will result in a loose bond between the crystal and amorphous interface, increase the resistance to charge transfer, and reduce the OER performance of the catalyst. When using two sacrificial template methods to prepare core-shell structure nanomaterials, the pyrolysis temperature needs to be strictly controlled, and due to the addition of H2, there are safety hazards in large-scale production. Summary of the invention
[0007] In view of the above-mentioned prior art, the present invention provides an aerogel catalyst with a core-shell structure and a preparation method and application thereof, so as to solve the technical problems that the preparation process of aerogel with a core-shell structure is complicated and the catalytic effect of the existing aerogel catalyst is poor.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is to provide a method for preparing an aerogel catalyst having a core-shell structure, comprising the following steps:
[0009] S1: dissolving ferric chloride hexahydrate and nickel chloride hexahydrate in water to obtain an aqueous solution of iron-nickel metal salts; dissolving dimethylamine borane in water to obtain an aqueous solution of dimethylamine borane;
[0010] S2: adding an aqueous solution of dimethylamine borane to an aqueous solution of an iron-nickel metal salt to obtain a mixed solution; the molar ratio of dimethylamine borane to nickel in the obtained mixed solution is 80-120:1;
[0011] S3: adding alkali solution to the mixed solution to obtain a nickel iron hydroxide colloidal solution;
[0012] S4: adding ruthenium acetate aqueous solution to the iron-nickel hydroxide colloidal solution, mixing well and sealing, incubating in a dark environment for 5 to 8 hours to obtain an iron-nickel-based nanocluster hydrogel; the molar ratio of the added ruthenium acetate to the nickel in the iron-nickel-based nanocluster hydrogel is 0.05 to 0.1:5;
[0013] S5: Washing and drying the iron-nickel based nanocluster hydrogel to obtain.
[0014] Based on the above technical solution, the present invention can also be improved as follows.
[0015] Furthermore, the molar ratio of iron to nickel in the iron-nickel metal salt aqueous solution is 2:5.
[0016] Furthermore, the concentration of iron in the iron-nickel metal salt aqueous solution is 0.01-0.02 mol / L.
[0017] Furthermore, the concentration of the dimethylamine borane aqueous solution was 5 mol / L.
[0018] Furthermore, the molar ratio of dimethylamine borane to nickel in the mixed solution is 100:1.
[0019] Furthermore, the alkali solution is a potassium hydroxide solution with a concentration of 1 M; the volume ratio of the added potassium hydroxide solution to the mixed solution is 1:50.
[0020] Furthermore, the concentration of the ruthenium acetate aqueous solution is 0.1-0.2 g / L; the volume ratio of the added ruthenium acetate aqueous solution to the mixed solution is 1:50-75.
[0021] Furthermore, in S4, the incubation temperature is 25° C. and the incubation time is 6 hours.
[0022] The invention also discloses an aerogel catalyst with a core-shell structure, which is prepared by adopting the above preparation method.
[0023] The invention also discloses the application of the aerogel catalyst with a core-shell structure in hydrogen production by electrolysis of water.
[0024] The beneficial effects of the present invention are:
[0025] 1. The present invention realizes the preparation of transition metal core-shell structure aerogel nanomaterials by wet chemical reduction method. By utilizing the mild reducing property of dimethylaminoborane and controlling the reaction time, FeNi3 alloy is slowly grown inside the iron-nickel hydroxide colloid, and the external iron-nickel hydroxide colloid is preserved, and finally a multiphase catalytic active site of nickel-iron-based core-shell structure is formed, generating an aerogel structure and core-shell mixed material.
[0026] 2. The present invention uses ferric chloride hexahydrate and nickel chloride hexahydrate as main raw materials, and by precisely controlling the reaction conditions, a high-purity innovative iron-nickel metal salt formula design can be obtained, realizing a convenient and quick one-step preparation of iron-nickel-based aerogel catalyst, and the introduction of potassium hydroxide realizes precise control of the iron-nickel element content, which is accurate. During the preparation process, FeNi3 crystals grow in situ inside the hydroxide, which can ensure the close integration of the interface of the core-shell structure, improve the stability of the structure and the catalytic efficiency, and the final catalyst has excellent catalytic performance.
[0027] 3. The present invention uses a trace amount of metallic ruthenium as a reaction initiator, which can effectively catalyze the reduction process, reduce the reaction activation energy, increase the reaction rate, and has time effectiveness.
[0028] 4. The present invention breaks the ideological and technical constraints of traditional aerogel preparation, realizes the morphological transformation from transition metal elements to core-shell aerogel, and innovates a new idea and method for preparing a core-shell structure aerogel with uniform particle size composited with multiple elements of iron, nickel, oxygen, and carbon. In addition, the catalyst synthesis process in the present invention is relatively simple, does not require complex equipment and cumbersome steps, and is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope photo of the aerogel catalyst with a core-shell structure in Example 1;
[0030] Figure 2 is the XRD diffraction pattern of the aerogel catalyst with a core-shell structure in Example 1;
[0031] Figure 3 is a transmission electron microscope photograph of the aerogel catalyst with a core-shell structure in Example 1;
[0032] Figure 4 This is a scanning electron microscope photo of the aerogel catalyst in Comparative Example 3;
[0033] Figure 5 is the XRD diffraction pattern of the aerogel catalyst in Comparative Example 3;
[0034] Figure 6 This is a transmission electron microscope photo of the aerogel catalyst in Comparative Example 3;
[0035] Figure 7 is the OER performance curve of the aerogel catalyst with a core-shell structure in Example 1;
[0036] Figure 8 This is the OER performance curve of the aerogel catalyst in Comparative Example 3. DETAILED DESCRIPTION
[0037] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0038] Example 1
[0039] An aerogel catalyst with a core-shell structure is prepared by the following steps:
[0040] S1: dissolving 2 mmol of ferric chloride hexahydrate in 50 mL of water to obtain a ferric chloride solution; dissolving 5 mmol of nickel chloride hexahydrate in 50 mL of water to obtain a nickel chloride solution; then pouring the ferric chloride solution and the nickel chloride solution into 50 mL of deionized water, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0041] S2: Under a 30° C. water bath condition, 0.5 mol of dimethylamine borane was dissolved in 100 mL of water to obtain a dimethylamine borane solution; then the dimethylamine borane solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0042] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0043] S4: 4 mL of 0.133 g / L ruthenium acetate (C 14 H 21 O 15 The Ru3) aqueous solution was added dropwise to the iron-nickel hydroxide colloid solution 4 times, 1 mL each time, with a 1-min interval in between. After the addition was completed, the iron-nickel hydroxide colloid was sealed and incubated at 25°C in a dark environment for 6 hours to obtain the iron-nickel based nanocluster hydrogel. When moving the colloid, move it slowly without shaking it violently.
[0044] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0045] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst with a core-shell structure.
[0046] Example 2
[0047] An aerogel catalyst with a core-shell structure is prepared by the following steps:
[0048] S1: dissolving 2 mmol of ferric chloride hexahydrate in 50 mL of water to obtain a ferric chloride solution; dissolving 5 mmol of nickel chloride hexahydrate in 50 mL of water to obtain a nickel chloride solution; then mixing the ferric chloride solution and the nickel chloride solution, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0049] S2: Under a 30° C. water bath condition, 0.4 mol of dimethylamine borane was dissolved in 100 mL of water to obtain a dimethylamine borane solution; then the dimethylamine borane solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0050] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0051] S4: 4 mL of 0.1 g / L ruthenium acetate (C 14 H 21 O 15 Ru3) aqueous solution was added to the mixed solution in 4 drops, 1 mL each time, with a 1-min interval in between. After the addition was completed, the iron-nickel hydroxide colloid was sealed and incubated at 25°C in a dark environment for 5 hours to obtain the iron-nickel based nanocluster hydrogel. When moving the colloid, move it slowly without shaking it violently.
[0052] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0053] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst with a core-shell structure.
[0054] Example 3
[0055] An aerogel catalyst with a core-shell structure is prepared by the following steps:
[0056] S1: dissolving 2 mmol of ferric chloride hexahydrate in 50 mL of water to obtain a ferric chloride solution; dissolving 5 mmol of nickel chloride hexahydrate in 50 mL of water to obtain a nickel chloride solution; then pouring the ferric chloride solution and the nickel chloride solution into 100 mL of deionized water, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0057] S2: Under a 30° C. water bath condition, 0.6 mol of dimethylamine borane was dissolved in 100 mL of water to obtain a dimethylamine borane solution; then the dimethylamine borane solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0058] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0059] S4: 4 mL of 0.2 g / L ruthenium acetate (C 14 H 21 O 15 Ru3) aqueous solution was added to the mixed solution in 4 drops, 1 mL each time, with a 1-min interval in between. After the addition was completed, the iron-nickel hydroxide colloid was sealed and incubated at 25°C in a dark environment for 5 hours to obtain the iron-nickel based nanocluster hydrogel. When moving the colloid, move it slowly without shaking it violently.
[0060] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0061] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst with a core-shell structure.
[0062] Comparative Example 1
[0063] An aerogel catalyst is prepared by the following steps:
[0064] S1: dissolving 2 mmol of ferric acetate in 50 mL of water to obtain a ferric acetate solution; dissolving 5 mmol of nickel acetate in 50 mL of water to obtain a nickel acetate solution; then pouring the ferric acetate solution and the nickel acetate solution into 50 mL of deionized water, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0065] S2: Under a 30° C. water bath condition, 0.5 mol of dimethylamine borane was dissolved in 100 mL of water to obtain a dimethylamine borane solution; then the dimethylamine borane solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0066] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0067] S4: 4 mL of 0.133 g / L ruthenium acetate (C 14 H 21 O 15 Ru3) aqueous solution was added dropwise to the mixed solution 4 times, 1 mL each time, with a 1-min interval in between. After the addition was completed, the iron-nickel hydroxide colloid was sealed and incubated at 25°C in a dark environment for 6 hours to obtain the iron-nickel based nanocluster hydrogel. When moving the colloid, move it slowly without shaking it violently.
[0068] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0069] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst.
[0070] Comparative Example 2
[0071] An aerogel catalyst is prepared by the following steps:
[0072] S1: dissolving 2 mmol of ferric chloride hexahydrate in 50 mL of water to obtain a ferric chloride solution; dissolving 5 mmol of nickel chloride hexahydrate in 50 mL of water to obtain a nickel chloride solution; then pouring the ferric chloride solution and the nickel chloride solution into 50 mL of deionized water, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0073] S2: Under a 30° C. water bath condition, 0.5 mol of sodium borohydride was dissolved in 100 mL of water to obtain a sodium borohydride solution; then the sodium borohydride solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0074] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0075] S4: 4 mL of 0.133 g / L ruthenium acetate (C 14 H 21 O 15 Ru3) aqueous solution was added dropwise to the mixed solution 4 times, 1 mL each time, with a 1-min interval in between. After the addition was completed, the iron-nickel hydroxide colloid was sealed and incubated at 25°C in a dark environment for 6 hours to obtain the iron-nickel based nanocluster hydrogel. When moving the colloid, move it slowly without shaking it violently.
[0076] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0077] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst.
[0078] Comparative Example 3
[0079] An aerogel catalyst is prepared by the following steps:
[0080] S1: dissolving 2 mmol of ferric chloride hexahydrate in 50 mL of water to obtain a ferric chloride solution; dissolving 5 mmol of nickel chloride hexahydrate in 50 mL of water to obtain a nickel chloride solution; then pouring the ferric chloride solution and the nickel chloride solution into 50 mL of deionized water, stirring evenly, to obtain an iron-nickel metal salt aqueous solution;
[0081] S2: Under a 30° C. water bath condition, 0.5 mol of dimethylamine borane was dissolved in 100 mL of water to obtain a dimethylamine borane solution; then the dimethylamine borane solution was immediately added to the iron-nickel metal salt aqueous solution to obtain a mixed solution;
[0082] S3: 5 mL of 1 M KOH solution was added dropwise to the mixed solution in 5 times, 1 mL each time, with a 1 min interval in between, to obtain a nickel iron hydroxide colloidal solution after the addition was completed;
[0083] S4: Seal the iron-nickel hydroxide colloid and incubate it in a dark environment at 25°C for 6 hours to obtain the iron-nickel based nanocluster hydrogel; move the colloid slowly without shaking it violently;
[0084] S5: Pour the obtained iron-nickel based nanocluster hydrogel into a 50 mL centrifuge tube and wash it three times. After each centrifugation, clean up the deionized water, add 30 mL of deionized water and centrifuge again. The centrifugation speed is 8000 rpm each time.
[0085] S6: The cleaned iron-nickel-based nanocluster hydrogel is placed in a freeze dryer and dried for 12 hours to obtain an aerogel catalyst.
[0086] Results Analysis
[0087] The aerogel catalysts with a core-shell structure prepared in Examples 1 to 3 have similar morphologies and properties. Taking the aerogel catalyst with a core-shell structure in Example 1 as an example, the morphology and properties of the catalyst are analyzed.
[0088] The aerogel catalyst with a core-shell structure obtained in Example 1 was analyzed by scanning electron microscopy, XRD and transmission electron microscopy, and the results were as follows: Figures 1 to 3 As shown. Figures 1 to 3 It can be seen that the aerogel catalyst prepared by the present invention is loose and porous, and has an interwoven three-dimensional structure ( Figure 1 ); and the aerogel catalyst exhibits strong diffraction peaks at 2-Theta diffraction angles of 44.2°, 51.5° and 75.8°, corresponding to the diffraction peaks of the FeNi3 alloy phase (1 11), (2 0 0) and (2 2 0) in the diffraction card PDF#00-038-0419, indicating that the obtained aerogel catalyst mainly appears in the FeNi3 phase ( Figure 2); TEM transmission microscope shows that the aerogel catalyst prepared by the present invention has two regions of low density and high density, and the high density region is wrapped by the low density region, presenting a core-shell structure as a whole ( Figure 3 ).
[0089] The morphologies of the catalysts in Comparative Examples 1 and 2 were also investigated. It was found that the aerogel catalysts prepared in Comparative Examples 1 and 2 did not have a core-shell structure. Compared with Example 1, the metal salt used in Comparative Example 1 was acetate (Chloride in Example 1), indicating that the preparation process of the present invention is not applicable to all metal salts, and only specific metal salts can form the desired morphology structure. Compared with Example 1, the reducing dimethylamine borane in Comparative Example 2 was replaced by sodium borohydride. Since the reducing property of sodium borohydride is much stronger than that of dimethylamine borane, iron and nickel will be reduced to iron-nickel alloy during the incubation process. Therefore, a core-shell structure is not formed in the end, but a large area of iron-nickel alloy is formed.
[0090] The aerogel catalyst obtained in Comparative Example 3 was analyzed by scanning electron microscopy, XRD and transmission electron microscopy, and the results were as follows: Figures 4 to 6 As shown. Figures 4 to 6 It can be seen that although the final aerogel catalyst also has a loose and porous aerogel structure ( Figure 4 ), however, no obvious characteristic diffraction peaks appeared in the sample prepared without adding Ru ions (labeled as Fe2Ni5), which indicates that the sample prepared without adding Ru ions is an amorphous structure ( Figure 5 ). Similarly, TEM transmission microscopy showed that the obtained sample did not have an obvious core-shell structure ( Figure 6 ).
[0091] In addition, the products prepared in Example 1 and Comparative Example 3 were used as catalysts to investigate the oxygen evolution performance of the electrolyzed water. Figure 7-8 As shown, Figure 7 is the OER performance curve of the catalyst obtained in Example 1, Figure 8 is the OER performance curve of the catalyst obtained in Comparative Example 3. Figure 7 It can be seen that by introducing Ru into the reaction system, a peak appears near 1.45 V on the X-axis of the OER performance curve of the final catalyst. The catalyst without introducing Ru into the reaction system also has a peak near 1.45 V, but the peak of the sample with Ru added appears faster, indicating that it has greater activity, and the Ni element in it is easier to transfer electrons to the O element, thereby producing oxygen more efficiently.
[0092] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing an aerogel catalyst having a core-shell structure, characterized in that: The following steps are involved: S1: dissolving ferric chloride hexahydrate and nickel chloride hexahydrate in water to obtain an iron-nickel metal salt aqueous solution; dissolving dimethylamine borane in water to obtain a dimethylamine borane aqueous solution; the molar ratio of iron to nickel in the iron-nickel metal salt aqueous solution is 2:5; S2: adding a dimethylamine borane aqueous solution to an iron-nickel metal salt aqueous solution to obtain a mixed solution; the molar ratio of dimethylamine borane to nickel in the obtained mixed solution is 80-120:1; S3: adding alkali solution to the mixed solution to obtain a nickel iron hydroxide colloidal solution; S4: adding ruthenium acetate aqueous solution to the iron-nickel hydroxide colloidal solution, mixing well and sealing, incubating in a dark environment for 5 to 8 hours to obtain an iron-nickel-based nanocluster hydrogel; the molar ratio of the added ruthenium acetate to the nickel in the iron-nickel-based nanocluster hydrogel is 0.05 to 0.1:5; S5: Washing and drying the iron-nickel based nanocluster hydrogel to obtain.
2. The method for preparing an aerogel catalyst having a core-shell structure according to claim 1, characterized in that: The concentration of iron in the iron-nickel metal salt aqueous solution is 0.01-0.02 mol / L.
3. The method for preparing an aerogel catalyst having a core-shell structure according to claim 2, characterized in that: The concentration of the dimethylamine borane aqueous solution is 5 mol / L.
4. The method for preparing an aerogel catalyst having a core-shell structure according to claim 3, characterized in that: The molar ratio of dimethylamine borane to nickel in the mixed solution is 100:
1.
5. The method for preparing an aerogel catalyst having a core-shell structure according to claim 4, characterized in that: The alkali solution is a potassium hydroxide solution with a concentration of 1M; the volume ratio of the added potassium hydroxide solution to the mixed solution is 1:
50.
6. The method for preparing an aerogel catalyst having a core-shell structure according to claim 5, characterized in that: The concentration of the ruthenium acetate aqueous solution is 0.1-0.2 g / L; the volume ratio of the added ruthenium acetate aqueous solution to the mixed solution is 1:50-75.
7. The method for preparing an aerogel catalyst having a core-shell structure according to claim 1, characterized in that: The incubation temperature in S4 was 25°C and the incubation time was 6 hours.
8. An aerogel catalyst having a core-shell structure, characterized in that: The method is prepared by any one of claims 1 to 7.
9. The use of the aerogel catalyst having a core-shell structure according to claim 8, characterized in that: Aerogel catalysts with core-shell structure are used for water electrolysis to produce hydrogen.
Citation Information
Patent Citations
Palladium-doped aluminum-cobalt-chromium-iron-nickel high-entropy alloy composite electrode and preparation method thereof
CN113224324A
Copper additive applied to thin film electroplating and electroplating process thereof
CN115449864A